The Ethical Dilemma of Lifestyle Change: Designing for sustainable schools and sustainable citizenship - Wheeler, Andrea (Les ateliers de l'éthique / The Ethics Forum)

(untitled) (Centre de recherche en éthique de l’Université de Montréal, 2009)
This paper explores how participation and sustainability are being addressed by architects within the Building Schools for the Future (BSF) programme in the UK. The intentions promoted by the programme are certainly ambitious, but the ways to fulfil these aims are ill-explored. Simply focusing on providing innovative learning technologies, or indeed teaching young people about physical sustainability features in buildings, will not necessarily teach them the skills they will need to respond to the environmental and social challenges of a rapidly changing world. However, anticipating those skills is one of the most problematic issues of the programme. The involvement of young people in the design of schools is used to suggest empowerment, place-making and to promote social cohesion but this is set against government design literature which advocates for exemplars, standard layouts and best practice, all leading to forms of standardisation. The potentials for tokenistic student involvement and conflict with policy aims are evident. This paper explores two issues: how to foster in young people an ethic towards future generations, and the role of co-design practices in this process. Michael Oakeshott calls teaching the conversation of mankind. In this paper, I look at the philosophy of Hannah Arendt, Emmanuel Levinas, Maurice Merleau-Ponty and Luce Irigaray to argue that investigating the ethical dilemmas of the programme through critical dialogue with students offers an approach to meeting government objectives, building sustainable schools, and fostering sustainable citizenship.